20‐Hydroxyecdysone stimulates nuclear accumulation of BmNep1, a nuclear ribosome biogenesis‐related protein in the silkworm, Bombyx mori. Issue 5 (22nd June 2016) - Ji, M.‐M.; Liu, A.‐Q.; Sima, Y.‐H.; Xu, S.‐Q.
Abstract: The pathway of communication between endocrine hormones and ribosome biogenesis critical for physiological adaptation is largely unknown. Nucleolar essential protein 1 ( Nep1 ) is an essential gene for ribosome biogenesis and is functionally conserved in many in vertebrate and invertebrate species. In this study, we cloned Bombyx mori Nep1 ( BmNep1 ) due to its high expression in silk glands of silkworms on day 3 of the fifth instar. We found that BmNep1 mRNA and protein levels were upregulated in silk glands during fourth‐instar ecdysis and larval–pupal metamorphosis. By immunoprecipitation with the anti‐BmNep1 antibody and liquid chromatography‐tandem mass spectrometry analyses, it was shown that BmNep1 probably interacts with proteins related to ribosome structure formation. Immunohistochemistry, biochemical fractionation and immunocytochemistry revealed that BmNep1 is localized to the nuclei in Bombyx cells. Using BmN cells originally derived from ovaries, we demonstrated that 20‐hydroxyecdysone (20E) induced BmNep1 expression and stimulated nuclear accumulation of BmNep1. Under physiological conditions, BmNep1 was also upregulated in ovaries during larval–pupal metamorphosis. Overall, our results indicate that the endocrine hormone 20E facilitates nuclear accumulation of BmNep1, which is involved in nuclear ribosome biogenesis in Bombyx .